In vivo neutron capture therapy of cancer using ultrasmall gadolinium oxide nanoparticles with cancer-targeting ability. Issue 2 (3rd January 2020) - Ho, Son Long; Choi, Garam; Yue, Huan; Kim, Hee-Kyung; Jung, Ki-Hye; Park, Ji Ae; Kim, Mi Hyun; Lee, Yong Jin; Kim, Jung Young; Miao, Xu; Ahmad, Mohammad Yaseen; Marasini, Shanti; et al.
Abstract : A cancer growth suppression was observed due to the GdNCT effects of the RGD-PAA-UGNPs. Abstract : Gadolinium neutron capture therapy (GdNCT) is considered as a new promising cancer therapeutic technique. Nevertheless, limited GdNCT applications have been reported so far. In this study, surface-modified ultrasmall gadolinium oxide nanoparticles (UGNPs) with cancer-targeting ability ( d avg = 1.8 nm) were for the first time applied to the in vivo GdNCT of cancer using nude model mice with cancer, primarily because each nanoparticle can deliver hundreds of Gd to the cancer site. For applications, the UGNPs were grafted with polyacrylic acid (PAA) for biocompatibility and colloidal stability, which was then conjugated with cancer-targeting arginylglycylaspartic acid (RGD) (shortly, RGD-PAA-UGNPs). The solution sample was intravenously administered into the tails of nude model mice with cancer. At the time of the maximum accumulation of the RGD-PAA-UGNPs at the cancer site, which was monitored using magnetic resonance imaging, the thermal neutron beam was locally irradiated onto the cancer site and the cancer growth was monitored for 25 days. The cancer growth suppression was observed due to the GdNCT effects of the RGD-PAA-UGNPs, indicating that the surface-modified UGNPs with cancer-targeting ability are potential materials applicable to the in vivo GdNCT of cancer.